Burnt sugarcane harvesting: Particulate matter exposure and the effects on lung function, oxidative stress, and urinary 1-hydroxypyrene - Prado, Gustavo Faibischew; Trevisan Zanetta, Dirce Maria; Arbex, Marcos Abdo; Braga, Alfesio Luis; Amador Pereira, Luiz Alberto; Rodrigues de Marchi, Mary Rosa [UNESP]; de Melo Loureiro, Ana Paula; Marcourakis, Tania; Sugauara, Lucy Elaine [UNESP]; Figaro Gattas, Gilka Jorge; Goncalves, Fernanda Toledo; Salge, Joao Marcos; et al. (Elsevier B.V., 2012)
Non-mechanised sugarcane harvesting preceded by burning exposes workers and the people of neighbouring towns to high concentrations of pollutants.This study was aimed to evaluate the respiratory symptoms, lung function and oxidative stress markers in sugarcane workers and the residents of Mendonca, an agricultural town in Brazil, during the non-harvesting and harvesting periods and to assess the population and individual exposures to fine particulate matter (PM2.5). Sugarcane workers and healthy volunteers were evaluated with two respiratory symptom questionnaires, spirometry, urinary 1-hydroxypyrene levels, and the measurement of antioxidant enzymes and plasma malonaldehyde during the non-harvesting and harvesting periods. The environmental assessment was determined from PM2.5 concentration.PM2.5 level increased from 8 mu g/m(3) during the non-harvesting period to 23.5 mu g/m(3) in the town and 61 mu g/m(3) on the plantations during the harvesting period. Wheezing, coughing, sneezing, and breathlessness increased significantly in both groups during the harvesting period, but more markedly in workers. A decrease in lung function and antioxidant enzyme activity was observed in both populations during harvesting; this decrease was greater among the sugarcane workers. The urinary 1-hydroxypyrene levels only increased in the sugarcane workers during the harvesting period. The malonaldehyde levels were elevated in both groups, with a higher increase observed in the workers.This research demonstrates the exposure of sugarcane workers and the inhabitants of a neighbouring town to high PM2.5 concentrations during the sugarcane harvest period. This exposure was higher among the sugarcane workers, as illustrated by both higher PM2.5 concentrations in the sugarcane fields and higher urinary 1-hydroxypyrene levels in the volunteers in this group. The higher incidence of respiratory symptoms, greater decrease in lung function and more marked elevation of oxidative stress markers among the sugarcane workers during the harvest confirms the greater effect magnitude in this population and a dose-dependent relationship between pollution and the observed effects. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Outdoor pollution; Biomass; Particulate matter; Sugarcane; Lung function; Oxidative stress